2014
DOI: 10.1111/jbfa.12077
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Executive Stock Option Backdating?

Abstract: We study motives for executive stock option backdating, the practice of changing the grant dates of current options to dates in the past using hindsight. We find that smaller, younger, and less profitable firms tend to be heavier involved in backdating. These results are consistent with the retention hypothesis. In line with the incentive hypothesis, we find that backdating occurs more for options that are out-of-the-money. We derive some evidence for the agency hypothesis, in the sense that backdating compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…All of the governance provisions are provided in the ISS/RiskMetrics data and the E Index is calculated from there. Prior studies that have used the Entrenchment Index as a proxy for corporate governance have shown that firms which score higher on the E Index are associated with lower creditor ratings, excessive CEO compensation, tax aggressiveness and lower firm valuations (see Alali et al, 2012;Brown & Caylor, 2006;Francis et al, 2013;Hoppe & Moers, 2011;Skantz, 2012;Veld & Wu, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…All of the governance provisions are provided in the ISS/RiskMetrics data and the E Index is calculated from there. Prior studies that have used the Entrenchment Index as a proxy for corporate governance have shown that firms which score higher on the E Index are associated with lower creditor ratings, excessive CEO compensation, tax aggressiveness and lower firm valuations (see Alali et al, 2012;Brown & Caylor, 2006;Francis et al, 2013;Hoppe & Moers, 2011;Skantz, 2012;Veld & Wu, 2013).…”
Section: Methodsmentioning
confidence: 99%